Compromissos assumidos por grandes e médias economias em acordos preferenciais de comércio: O contraponto entre uniao Europeia e estados unidos e China e Índia - Michelle Ratton Sanchez Badin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– Ten to fifteen new preferential trade agreements are notified to the World Trade Organization transparency mechanism each year. As of May 2011, WTO secretariat calculated that 297 of all agreements were in force. Major economies have always been appointed as the leaders of this movement, but medium-size economies are increasingly occupying a space in this scenario. This article aims at mapping the themes covered by the agreements of the two largest economies, the European Union and the United States of America, in contrast with selected agreements of two medium-size economies, India and China, in order to the regulatory trends in these agreements. One hypothesis of this paper is that medium-size economies' preferential agreements may provide regulatory innovations, especially on their relationship with the multilateral trade system.
Keywords: K33; 330